HADIS TENTANG PEMBERIAN UPAH : Studi Kasus Pemberian Upah Karyawan Di Yatim Mandiri Kota Kediri Berdasarkan Fatwa DSN MUI No: 09/DSN-MUI/IV/2000 - Madyasari, Arlupi; Khamim, Khamim (Holistic al-Hadis, 2023)
This research aims to analyze hadiths related to giving wages to employees, with a focus on case studies in Yatim Mandiri, Kediri City. This research also refers to the DSN MUI Fatwa No: 09/DSN-MUI/IV/2000 which provides guidelines regarding the provision of wages from an Islamic religious perspective. The research method used is library research, by collecting hadiths related to wages from the main hadith books and examining the DSN MUI Fatwa No: 09/DSN-MUI/IV/2000. Apart from that, this research also involved interviews with management and employees at Yatim Mandiri Kediri City to get their direct perspective. The research results show that in Islam, giving wages to employees is considered an obligation that must be carried out honestly and fairly. The hadiths related to this issue stress the importance of providing wages commensurate with the work done, fulfilling employees' rights, and avoiding lying to them. DSN MUI Fatwa No: 09/DSN-MUI/IV/2000 also provides specific guidelines regarding the provision of wages to employees, including regulating the amount of wages, timely payment, and protecting employee rights. The case study at Yatim Mandiri Kediri City shows that the payment of wages to employees at this institution has followed the guidelines set out in the DSN MUI Fatwa No: 09/DSN-MUI/IV/2000.